2007
DOI: 10.1073/pnas.0610081104
|View full text |Cite|
|
Sign up to set email alerts
|

New directions in single-molecule imaging and analysis

Abstract: Optical imaging and analysis of single molecules continue to unfold as powerful ways to study the individual behavior of biological systems, unobscured by ensemble averaging. Current expansion of interest in this field is great, as evidenced by new meetings, journal special issues, and the large number of new investigators. Selected recent advances in biomolecular analysis are described, and two new research directions are summarized: superresolution imaging using single-molecule fluorescence and trapping of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
334
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(343 citation statements)
references
References 128 publications
2
334
0
7
Order By: Relevance
“…SMLM can resolve biological structures at the nanometer scale (typically 20 nm lateral resolution), circumventing Abbe's diffraction limit. At the cost of a relatively simple setup 6,7 , it has opened exciting new opportunities in life science research 8,9 .The underlying principle of SMLM is the sequential imaging of sparse subsets of fluorophores distributed over thousands of frames, to populate a high-density map of fluorophore positions. Such large data sets require automated image-analysis algorithms to detect and precisely infer the position of individual fluorophore, taking advantage of their separation in space and time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SMLM can resolve biological structures at the nanometer scale (typically 20 nm lateral resolution), circumventing Abbe's diffraction limit. At the cost of a relatively simple setup 6,7 , it has opened exciting new opportunities in life science research 8,9 .The underlying principle of SMLM is the sequential imaging of sparse subsets of fluorophores distributed over thousands of frames, to populate a high-density map of fluorophore positions. Such large data sets require automated image-analysis algorithms to detect and precisely infer the position of individual fluorophore, taking advantage of their separation in space and time.…”
mentioning
confidence: 99%
“…SMLM can resolve biological structures at the nanometer scale (typically 20 nm lateral resolution), circumventing Abbe's diffraction limit. At the cost of a relatively simple setup 6,7 , it has opened exciting new opportunities in life science research 8,9 .…”
mentioning
confidence: 99%
“…Apart from biological applications, single-molecule spectroscopy has provided exceptional insights into the properties of soft and complex materials, and holds great promise for further development in this fi eld. For recent reviews, see Refs [3][4][5][6][7][8]. Th ere will, no doubt, be further qualitative progress related to recently developed super-resolution microscopic techniques [9][10], which overcome the diff raction limit in optical imaging and bring the resolution closer to the molecular scale.…”
mentioning
confidence: 99%
“…Steps toward super-resolution with single-molecule emitters. For acronyms, see (139) In 1995, after spending years developing near-field optical imaging at Bell Labs, Eric Betzig wrote a seminal paper noting that a control variable that distinguishes molecules along another dimension could be used for superresolution microscopy, and he suggested the use of many molecules with different colors, as in the low temperature studies (131). Subsequently, in 1998 Antoine van Oijen et al experimentally demonstrated this idea directly: they used spectral tunability at low temperatures to spatially resolve a set of single molecules in three dimensions, with 40 nm lateral and 100 nm axial resolution, far below the optical diffraction limit (132,133).…”
Section: Key Proposalmentioning
confidence: 99%